2015
DOI: 10.1037/a0038693
|View full text |Cite
|
Sign up to set email alerts
|

Random walks on semantic networks can resemble optimal foraging.

Abstract: When people are asked to retrieve members of a category from memory, clusters of semantically related items tend to be retrieved together. A recent article by Hills, Jones, and Todd (2012) argued that this pattern reflects a process similar to optimal strategies for foraging for food in patchy spatial environments, with an individual making a strategic decision to switch away from a cluster of related information as it becomes depleted. We demonstrate that similar behavioral phenomena also emerge from a random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
218
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 154 publications
(226 citation statements)
references
References 40 publications
7
218
0
1
Order By: Relevance
“…Traditionally, semantic fluency data has been explained as the result of a two-stage retrieval process, where participants switch between a global cue (e.g., animals) and local cue (e.g., pets) in a spatial representation when searching for category members (Hills et al 2012). However, it has also been shown that semantic fluency data can be explained by a single-stage retrieval process on a different semantic representation: a censored random walk on a semantic network (Abbott et al 2015). Under this model, fluency data is generated by traversing edges at random in a semantic network.…”
Section: Semantic Fluency Taskmentioning
confidence: 99%
See 4 more Smart Citations
“…Traditionally, semantic fluency data has been explained as the result of a two-stage retrieval process, where participants switch between a global cue (e.g., animals) and local cue (e.g., pets) in a spatial representation when searching for category members (Hills et al 2012). However, it has also been shown that semantic fluency data can be explained by a single-stage retrieval process on a different semantic representation: a censored random walk on a semantic network (Abbott et al 2015). Under this model, fluency data is generated by traversing edges at random in a semantic network.…”
Section: Semantic Fluency Taskmentioning
confidence: 99%
“…Recent work in psychology has identified several potential process models (Abbott et al 2015;Hills et al 2012;Zemla and Austerweil 2017) that generate clustered fluency data. We propose a technique that capitalizes on these advances by inverting a process model used to simulate fluency data-specifically, the censored random walk model of search on a semantic network (Abbott et al 2015).…”
Section: U-invitementioning
confidence: 99%
See 3 more Smart Citations